Ecore representation for extending PNML for input-output place-transition nets - Moutinho, F. (2013)
This paper presents a metamodel for the Input-Output Place-Transition nets (IOPT nets), a Petri net class targeted at controllers modeling. The proposed metamodel reuses many of the elements of the Petri Net Markup Language (PNML) metamodel, such as places, transitions, and arcs; it extends the PNML metamodel for Place/Transition nets to comprise concepts inherent to IOPT nets. The IOPT nets metamodel is described in Ecore format, putting IOPT nets in the puzzle of MDA artifacts taking benefit from the MDA infrastructure.